Navigating the Emotional Classroom: How experience shapes educators' anxiety and self-worth - Rus, Mihaela; Neculai, Camelia; Sandu, Mihaela Luminița; Tănase, Tasențe (Technium Social Sciences Journal, 2023)
Most of the teaching staff agrees that traits such as "personality" or "mental integrity", along with behavioral manifestations, show substantial significance in the context of the classroom; some of them might even argue that these character attributes have a higher relevance than competence in the specialized field or teaching skills themselves. When an educator experiences failures, they are often attributed to inadequacies of a personal nature, including but not limited to suboptimal empathy, excessive or insufficient enthusiasm, or, as appropriate, excessive authoritarianism, inflexibility, or, conversely, excessive permissiveness. The sphere of stress, tension and anxiety, respectively, within the teaching body is configured as a compartment of the personality and mental health of teachers, which has been almost neglected from a cause-effect relationship perspective. Many postgraduate protagonists went to great lengths to emphasize that dealing with and managing anxiety turned out to be experiences of exceptional significance in the context of their subsequent professional work. A substantial segment of this population showed a strong inclination towards careful consideration of anxiety as a central theme in the educational sphere. As a comprehensive entity, frequently accompanied by an implicit nuance or predispositional character (ie, acting as an internal cause of manifested behavior), anxiety lends itself to multiple operational definitions. The prevalence of various forms of emotional maladjustment, especially anxiety, among the teaching staff has been a subject of sustained research since the first decades of this century. Self-esteem is a trait dedicated to the individual characteristic affective evaluation of one's own person. It is assumed that the level of self-efficacy of the teaching staff is influenced by the degree of self-esteem they show. Thus, the hypothesis is drawn that self-esteem plays an essential role in the academic itinerary of the teachers. A positive self-evaluation intrinsically facilitates the individual's professional development, translated into visible and consistent performance over the relevant time period.